Avaliação do trespasse vertical interincisivos na dentadura decídua, em pacientes com ceceio anterior e/ou projeção lingual anterior, na emissão dos fonemas linguoalveolares /t/, /d/, /n/ e /l/. - Sahad, Marcelo de Gouveia (2006)
Through a transversal epidemiological study, conducted in 333 Brazilian children, males (157) and females (176), aged 3 to 6 years old, enrolled in a public preschool in the city of São Paulo, this study aimed to evaluate the prevalence of the different kinds of vertical interincisal trespass and the relationship between these occlusal aspects with anterior lisping and/or anterior tongue thrust in the articulation of the lingua-alveolar phonemes /t/, /d/, /n/ and /l/. All children involved were submitted to a vertical interincisal trespass examination and to a phonoaudiologic evaluation. Besides the descriptive statistical analysis, including the calculation and tabulation of prevalence of the four kinds of vertical interincisal trespass (normal overbite, deep overbite, edge to edge and open bite), in percentual terms, the statistical significance was analyzed through the qui-square test, at a significance level of 0.05 (95% confidence limits), in order to check possible associations between the studied speech problems and the different kinds of vertical interincisal trespass. The quantitative analysis of the data demonstrated the following prevalences: 1- the different kinds of vertical interincisal trespass: 48.30% for normal overbite, 22.50% for deep overbite, 9.30% for edge to edge and 19.80% for open bite; 2- interdental lisping in relationship to the different kinds of vertical interincisal trespass: 42% for normal overbite, 12.50% for deep overbite, 12.50% for edge to edge and 33.30% for open bite; and 3- children with anterior tongue thrust in the articulation of the lingua-alveolar phonemes in relationship to the different kinds of vertical interincisal trespass: 42.10% for normal overbite, 14.% for deep overbite, 10.50% for edge to edge and 33.30% for open bite. The statistical analysis of the data demonstrated that there was a significance for individuals with anterior lisping and anterior tongue trust, in the articulation of the lingua-alveolar phonemes /t/, /d/, /n/ and /l/, regarding the open bite; and there was a statistical significance for individuals without anterior lisping and anterior tongue trust, in the articulation of the lingua-alveolar phonemes /t/, /d/, /n/ and /l/, regarding the deep overbite.